A comprehensive review on CHB MLI based PV inverter and feasibility study of CHB MLI based PV-STATCOM. (October 2017) - Sridhar, V.; Umashankar, S.
Abstract: A conventional grid-connected solar Photovoltaic (PV) inverter consists of Two-Level or Three-Level configuration is not suitable for very high power ratings and the size of AC side filter required is high to maintain the power quality as per the grid codes. It is inefficient in extracting maximum power as the tracking of Maximum power point is carried out for entire PV arrays connected together instead of independent MPPT of each PV array. With a conventional PV inverter, the utilization factor is also very less, since the system will be in idle state during night times or when the irradiation is weak. Hence a conventional solar inverter consists of Two-Level or Three-Level inverter suffers from the following drawbacks (a) Not suitable for very high Power Ratings (b) High filter size (c) Inefficient in harvesting maximum power (d) Less utilization factor. In this study, the need for the multilevel inverter (MLI) to minimize the drawbacks of the conventional inverter is discussed. Cascaded H-Bridge (CHB) configuration which is more preferred for solar power applications where isolated input DC sources are available and for STATCOM applications where there is no requirement of DC Sources is discussed in detail. The basic operation of CHB inverter, PWM techniques, and fault tolerant operations are explained through simulation results. The Independent MPPT control of each PV array using CHB inverter is reviewed. CHB inverter controls for PV applications and STATCOM applications are also reviewed. The concept of a PV-STATCOM which is required for improving the utilization factor of PV inverter is reviewed. The operation of PV-STATCOM is explained through simulation studies. Real and reactive power flow through a 11-Level, CHB MLI is verified through experimental results. Feasibility study for multilevel PV-STATCOM for High power applications using CHB configuration is carried out in this paper. Highlights: Basic concept of PV-STATCOM is reviewed and discussed. PWM methods, Fault redundant methods of Cascaded H-Bridge multi level inverters are briefly explained. Applications of Cascaded H-Bridge multi level inverters for Solar applications and STATCOM applications is reviewed and discussed. Control algorithms for Cascaded H-Bridge multi level inverter based PV Inverters are presented. Feasibility of Cascaded H-Bridge multi level inverter based PV-STATCOM is discussed.